SIGNIFICANCE OF MARBLE AND PORTLAND CEMENT - Dewangan, Arvind; Gupta, D.P. (International Journal of Engineering Technologies and Management Research, 2018)
The aim of this current study is both to avoid the environmental. In this way, we will help to protect the environment by consuming the waste marble dust obtained as a by- product of marble sawing and shaping processes in the factories those operating in our region. Stone industry is an important factor in worldwide economy. Despite this, a large amount of residues is produced in ornamental stone industry with different dimension and particle size. The increasing rate at which raw material are continuously transformed into industrial products results in waste generation. Consequently, recycling of industrial wastes and byproducts is becoming a crucial demand by the environmental laws in agreement with the concept of sustainable development. The present study was therefore planned to explore the possibility of usage of waste marble powder (WMP) as partial replacement of sand for production of concrete This research work is concerned with the experimental investigation on strength of concrete and optimum percentage of the partial replacement by replacing (OPC) cement via 0%, 10%, 12.5%, 15%, 17.5% and 20% of stone waste. Keeping all this view, the aim of the investigation is the behavior of concrete while replacing of waste with different proportions of stone waste in concrete by using tests like compression strength.